Mass screening of hepatitis B and C in Burkina Faso: seroprevalence update and impact of hepatitis B vaccine - Sanou, Armel Moumouni; Napon-Zongo, Delphine; Coulibaly, Abou; Traore, Ina Marie Angèle; Ouattara, Ad Bafa Ibrahim; Ilboudo, Abdoul Kader; Zoure, Abdou Azaque; Zida, Sylvie; Ouattara, Mathuola Nina Geneviève; Dera, Abdoulaye; Konate, Djara; Kyelem, Eric; et al. (The Journal of Infection in Developing Countries, 2024)
Introduction: Updated data on the seroprevalences of hepatitis B and C viruses (HBV, HCV) are required to enable the adaptation of control strategies. In this study, we aimed to: (i) estimate the seroprevalences of HBsAg carriers and HCV exposure in the general population, and (ii) determine the impact of vaccination on HBV circulation since its introduction in 2006 in the Expanded Program on Immunization (EPI). Methodology: From October 2020 to October 2022, a mass screening campaign was conducted in 10 cities across Burkina Faso. Individuals of all ages and genders who consented to participate were screened for viral markers (HBsAg, anti-HCV) using rapid diagnostic tests. The proportions of HBsAg carriers and HCV exposure were calculated using Stata, and logistic regression was used to assess the impact of HBV vaccination on HBsAg carriage. Results: A total of 15,650 participants were enrolled in the study. Of these, 51.4% were women and the age range was from 1 to 97 years. All participants were screened for HBsAg and 7,507 were also screened for anti-HCV. Overall, the seroprevalence of HBsAg was 8.8% and 2.6% for anti-HCV. The results indicated that age, gender, and place of residence were associated with HBV infection. Conclusions: The prevalence of HBV and HCV infections remains high in Burkina Faso. Prevention strategies, including initial mass screening with rapid diagnostic tests and vaccination, need to be intensified.